Prokaryotic Response to Phytodetritus-Derived Organic Material in Epi- and Mesopelagic Antarctic Waters - Manna, Vincenzo; Malfatti, Francesca; Banchi, Elisa; Cerino, Federica; De Pascale, Fabio; Franzo, Annalisa; Schiavon, Riccardo; Vezzi, Alessandro; Del Negro, Paola; Celussi, Mauro (Frontiers in Microbiology, 2020)
Particulate organic matter (POM) export represents the underlying principle of the biological carbon pump, driving the carbon flux from the sunlit to the dark ocean. The efficiency of this process is tightly linked to the prokaryotic community, as >70% of POM respiration is carried out by particle-associated prokaryotes. In the Ross Sea, one of the most productive areas of the Southern Ocean, up to 50% of the surface primary production is exported to the mesopelagic ocean as POM. Recent evidence suggests that a significant fraction of the POM in this area is composed of intact phytoplankton cells. During austral summer 2017, we set up bottle enrichment experiments in which we amended free-living surface and deep prokaryotic communities with organic matter pools generated from native microplankton, mimicking the particle export that may derive from mild (1 µg of Chlorophyll a L-1) and intense (10 µg of Chlorophyll a L-1) phytoplankton bloom. Over a course of four days, we followed free-living and particle-attached prokaryotes’ abundance, the degradation rates of polysaccharides, proteins and lipids, heterotrophic production as well as inorganic carbon utilization and prokaryotic community structure dynamics. Our results showed that several rare or undetected taxa in the initial community became dominant during the time course of the incubations and that different phytodetritus-derived organic matter sources induced specific changes in microbial communities, selecting for peculiar degradation and utilization processes spectra. Moreover, the features of the supplied detritus (in terms of microplankton taxa composition) determined different colonization dynamics and organic matter processing modes. Our study provides insights into the mechanisms underlying the prokaryotic utilization of phytodetritus, a significant pool of organic matter in the dark ocean